Outcome of advanced epithelial ovarian cancer: a tertiary care centre study - Umrethwala, Sakina Muslim; Shaikh, Sohel; Tatyabe Palve, Tushar; Devnikar, Komal; Kulkarni, Sejal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Ovarian cancer is the fourth most common cancer in Indian women with an incidence of 4.9 cases per 100,000. Epithelial ovarian cancer is a silent killer disease as it presents at an advanced stage with minimal signs and symptoms. Methods: It is a type of research article. The present study was conducted in Department of Obstetrics and Gynecology, Cama and Albless Hospital, Mumbai, Maharashtra, India, from a period of January 2018 to July 2019, during which 53 cases of EOC were studied. Results: Out of 53 cases of EOC, 45 cases were advanced stage EOC, they were either operated as PDS-ACT or NACT- IDS. Conclusions: NACT is recommended wherein optimal cytoreduction appears unlikely, or in patients where upfront surgery is high risk and extensive causing high morbidity post-surgery. Places where there is non-availability of special surgical expertise and hospital resources, there too NACT-IDS is recommended.